Analisis Kandungan Informasi Dividen dan Ketepatan Reaksi Pasar : Pengujian terhadap Dividend Signaling Theory Studi Empiris di Bursa Efek Jakarta - Sujoko, .; HM, Jogiyanto (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2001)
The purpose of this study is to examine the information content of dividend. Another purpose of this study is to examine the decisionally efficient market. This research explored the issue by applying the event study methodology for analyzing the market reaction. As much as 150 firms listed in Jakarta Stock Exchange (BEJ) were taken as a sample using a purposive sampling method. The sample are dividend into four sub sample: (1) sub sample consist of 150 firms that pay increase dividend, (2) sub sample consist of 18 firms that pay consistently increase dividend, (3) sub sample consist of 96 firms that pay increase dividend and the firms are growing, (4) sub sample consist of 54 firms that pay increase dividend and the firms are not growing. The statistic method used to test hypotheses is t-test. Three models of expected return were considered: OLS Market Model, Mean Adjusted Model, and Market Adjusted model. The empirical result indicates that dividend conveys information to the market. this means that investors in BEJ use information of dividend announcements for decision making. The result of this study supports dividend signaling theory. Another result of this study indicates that the Jakarta Stock Exchange (BEJ) is not decisionally efficient market. This means that investors are not sophisticated and fooled by manager of the firms.